The Strawberry Girl - Guenther, Shawna (Cuizine, 2025)
I wrote this piece when I lived in Saskatchewan and visited my parents in Halifax. With the increasing distribution of GMO fruits and vegetables in megastores, this story brings us back to the most important source of food in Canada: the local small farming community.